2013
DOI: 10.1038/hr.2013.107
|View full text |Cite
|
Sign up to set email alerts
|

The possibility of resistant hypertension during the treatment of hypertensive patients

Abstract: Patients with poorly controlled hypertension despite taking at least three different kinds of anti-hypertensive drugs, including diuretics, are considered to have resistant hypertension (RH). The prevalence of RH was reported to be 13% in the Japanese J-HOME study. The incidences of RH in younger and older Japanese individuals should be prospectively investigated in the near future. RH is associated with poor outcomes and various cardiovascular events. In addition, it is frequently associated with older age, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…A Spanish registry [24] and a USA cross-sectional study [25] found around 12% of hypertensive patients met the criteria for RH. In Asian, the Japanese J-HOME study reported a prevalence of RH of 13% [26]. Our cohort showed a similar finding that 14.6% of the hypertensive patients in Taiwan met the definition of RH.…”
Section: Discussionsupporting
confidence: 85%
“…A Spanish registry [24] and a USA cross-sectional study [25] found around 12% of hypertensive patients met the criteria for RH. In Asian, the Japanese J-HOME study reported a prevalence of RH of 13% [26]. Our cohort showed a similar finding that 14.6% of the hypertensive patients in Taiwan met the definition of RH.…”
Section: Discussionsupporting
confidence: 85%
“…Oral contraceptive use was associated with greater GC sensitivity in response to a laboratory stressor in women (Rohleder et al, 2003), which could not be further explored in our study. In addition, as hypertension has been observed in hypercortisolemia (Nishikawa et al, 2013), BP is also a documented correlate with HPA dysregulation. Thus, certain demographic basic health characteristics should be considered in deciphering the depression-obesity-GC resistance.…”
Section: Discussionmentioning
confidence: 95%
“…2 Despite the use of generally effective antihypertensive therapy, blood pressure (BP) often remains above target levels because of poor adherence, an inadequate treatment regimen and/or treatment resistance. 3 Resistant hypertension is currently defined as the failure to achieve a goal of BPo140/90 mm Hg in patients who are compliant with the maximal tolerated doses of a minimum of three antihypertensive drugs, one of which is a diuretic. The prevalence of resistant hypertension is unknown, but clinical trials suggest that it is not rare and may involve perhaps 20-30% of the study participants.…”
Section: Introductionmentioning
confidence: 99%